Mechanical stimulation controls osteoclast function through the regulation of Ca2+-activated Cl− channel Anoctamin 1 - Weijia Sun; Yuheng Li; Jianwei Li; Yingjun Tan; Xinxin Yuan; Haoye Meng; Jianting Ye; Guohui Zhong; XiaoYan Jin; Zizhong Liu; Ruikai Du; Wenjuan Xing; et al. (Communications Biology, 2023)
Abstract Mechanical force loading is essential for maintaining bone homeostasis, and unloading exposure can lead to bone loss. Osteoclasts are the only bone resorbing cells and play a crucial role in bone remodeling. The molecular mechanisms underlying mechanical stimulation-induced changes in osteoclast function remain to be fully elucidated. Our previous research found Ca2+-activated Cl− channel Anoctamin 1 (Ano1) was an essential regulator for osteoclast function. Here, we report that Ano1 mediates osteoclast responses to mechanical stimulation. In vitro, osteoclast activities are obviously affected by mechanical stress, which is accompanied by the changes of Ano1 levels, intracellular Cl− concentration and Ca2+ downstream signaling. Ano1 knockout or calcium binding mutants blunts the response of osteoclast to mechanical stimulation. In vivo, Ano1 knockout in osteoclast blunts loading induced osteoclast inhibition and unloading induced bone loss and. These results demonstrate that Ano1 plays an important role in mechanical stimulation induced osteoclast activity changes.